Immunology : a short course - Coico, Richard; Sunshine, Geoffrey (Hoboken, N.J : Wiley-Blackwell, 2009)
Contents: Overview of the immune system -- Elements of innate and acquired immunity -- Immunogens and antigens -- Antibody structure and function -- Antigen-antibody interactions, immune assays, and experimental systems -- The genetic basis of antibody structure -- Biology of the B lymphocyte -- Role of the major histocompatibility complex in the immune response -- Biology of the T lymphocyte -- Activation and function of T and B cells -- Cytokines -- Tolerance and autoimmunity -- Complement -- Hypersensitivity : type I -- Hypersensitivity : types II and III -- Hypersensitivity : type IV -- Immunodeficiency disorders and neoplasias of the lymphoid system -- Transplantation -- Tumor immunology -- Resistance and immunization to infectious diseases.
Previous ed.: New York; Chichester, Wiley, 2003. Includes bibliographical references and index.
Keywords: Immunology; Allergy and Immunology; Immunity